French all-in-one for dummies - Kurbegov, Eliane (--For dummies., 2012)
Your comprehensive guide to speaking, reading, and writing in French French is a beautiful language but can be quite difficult to learn. Whether you need to learn the language for a French class, or for business or leisure travel, French for Dummies All-In-One makes it easier. With nearly 800 pages, French All-in-One For Dummies is for those readers looking for a comprehensive guide to help them immerse themselves in the French language. Culls vital information from several Dummies titles, offering you a comprehensive, all-encompassing guide to speaking and using French. Includes French Canadian.